2018
DOI: 10.3791/57892
|View full text |Cite
|
Sign up to set email alerts
|

A 3-dimensional (3D)-printed Template for High Throughput Zebrafish Embryo Arraying

Abstract: The zebrafish is a globally recognized fresh water organism frequently used in developmental biology, environmental toxicology, and human disease related research fields. Thanks to its unique features, including large fecundity, embryo translucency, rapid and simultaneous development, etc., zebrafish embryos are often used for large scale toxicity assessment of chemicals and drug/compound screening. A typical screening procedure involves adult zebrafish spawning, embryos selection, and arraying the embryos int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The healthy AB wild-type embryos at 4 h post fertilization (hpf) were placed in 6-well and 96-well plates for chemical exposure according to the protocol established previously . Each chemical underwent a wide dose–response assessment based on the reported literatures, and the half-maximal effective concentration (EC 50 ) and half-maximal lethal concentration (LC 50 ) of each chemical were determined accordingly. ,,, The exposure concentrations were as follows: perfluorooctanesulfonate (PFOS, 2.0, 4.0, 8.0, 10.0, 12.0 μM), bisphenol A (BPA, 5.0, 10.0, 16.0, 20.0, 25.0 μM), cadmium chloride (CdCl 2 , 1.0, 2.0, 5.0, 10.0, 20.0 μM), lead iodide (PbI 2 , 0.2, 2.0, 5.0, 10.0, 20.0 μM), acetaminophen (APAP, 0.4, 0.8, 1.2, 1.6, 2.0 mM), 2,7-dibromocarbazole (27-DBCZ, 0.05, 0.1, 0.5, 1.25, 2.5 μM), 3-monobromocarbazo (3-BCZ, 1.0, 2.5, 5.0, 10.0, 25.0 μM), 3,6-dibromocarbazole (36-DBCZ, 1.0, 1.5, 2.0, 2.5, 5.0 μM), and 1,3,6,8-tetrabromocarbazo (1368-TBCZ, 1.0, 10.0, 50.0, 100.0, 250.0 μM).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The healthy AB wild-type embryos at 4 h post fertilization (hpf) were placed in 6-well and 96-well plates for chemical exposure according to the protocol established previously . Each chemical underwent a wide dose–response assessment based on the reported literatures, and the half-maximal effective concentration (EC 50 ) and half-maximal lethal concentration (LC 50 ) of each chemical were determined accordingly. ,,, The exposure concentrations were as follows: perfluorooctanesulfonate (PFOS, 2.0, 4.0, 8.0, 10.0, 12.0 μM), bisphenol A (BPA, 5.0, 10.0, 16.0, 20.0, 25.0 μM), cadmium chloride (CdCl 2 , 1.0, 2.0, 5.0, 10.0, 20.0 μM), lead iodide (PbI 2 , 0.2, 2.0, 5.0, 10.0, 20.0 μM), acetaminophen (APAP, 0.4, 0.8, 1.2, 1.6, 2.0 mM), 2,7-dibromocarbazole (27-DBCZ, 0.05, 0.1, 0.5, 1.25, 2.5 μM), 3-monobromocarbazo (3-BCZ, 1.0, 2.5, 5.0, 10.0, 25.0 μM), 3,6-dibromocarbazole (36-DBCZ, 1.0, 1.5, 2.0, 2.5, 5.0 μM), and 1,3,6,8-tetrabromocarbazo (1368-TBCZ, 1.0, 10.0, 50.0, 100.0, 250.0 μM).…”
Section: Methodsmentioning
confidence: 99%
“…High-throughput screening (HTS) implemented in the pharmaceutical discovery and drug screening industries shows promise in tackling this problem . Streamlining and automation of experimental procedures coupled with high-content imaging and computer analysis tools were developed to speed up the in vitro toxicity screening. Progressively, in vivo animal models such as zebrafish have demonstrated early success in performing rapid toxicity screening of engineered nanomaterials and ToxCast chemicals based on multiple phenotypic abnormalities. As the toxicity screening on 1060 ToxCast compounds performed by Truong et al suggested, the mode-of-actions and toxicity mechanisms revealed by the zebrafish model were highly conserved across environmental species and humans . Zebrafish HTS is poised to fill the data gap in the risk assessment of chemicals and emerging pollutants. , However, to achieve high-throughput level, it is critical to resolve the rate-limiting factor of the laborious morphometric analysis of microscopic images obtained.…”
Section: Introductionmentioning
confidence: 99%